2009
DOI: 10.3899/jrheum.081025
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Reconstitution after Autologous Hematopoietic Stem Cell Transplantation in Patients with Systemic Sclerosis: Relationship Between Clinical Benefits and Intensity of Immunosuppression

Abstract: Our results suggest that immunosuppression intensity, sufficient to induce transient suppression of thymic function, is attributable to the feasible clinical response in patients with SSc treated with autologous HSCT. Appropriate monitoring of sjTREC values may predict clinical benefits in transplanted SSc patients after autologous HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
3
22
0
5
Order By: Relevance
“…The immune reconstitution process after aHSCT is associated with the reemergence of naive T cells, the depletion of autoreactive memory T cells, the regeneration of thymic-derived FoxP3 þ regulatory T cells and the recovery of the naive B-cell compartment. 29,30,35,38 Two important observations for SSc patients treated by aHSCT emerged from the present pilot study: first, both nTreg and aTreg cells regenerated to frequencies comparable with those in normal controls; second, the renewal of Treg subsets was associated with a restoration of nTreg suppressive capacity, as reported by Zhang et al 34 in SLE patients treated by aHSCT. Altogether, our data support the 'resetting' of the adaptive immune system induced by aHSCT, as previously reported for other types of autoimmune diseases treated by aHSCT and always based on the analysis of a small number of patients.…”
Section: Controlsupporting
confidence: 77%
See 2 more Smart Citations
“…The immune reconstitution process after aHSCT is associated with the reemergence of naive T cells, the depletion of autoreactive memory T cells, the regeneration of thymic-derived FoxP3 þ regulatory T cells and the recovery of the naive B-cell compartment. 29,30,35,38 Two important observations for SSc patients treated by aHSCT emerged from the present pilot study: first, both nTreg and aTreg cells regenerated to frequencies comparable with those in normal controls; second, the renewal of Treg subsets was associated with a restoration of nTreg suppressive capacity, as reported by Zhang et al 34 in SLE patients treated by aHSCT. Altogether, our data support the 'resetting' of the adaptive immune system induced by aHSCT, as previously reported for other types of autoimmune diseases treated by aHSCT and always based on the analysis of a small number of patients.…”
Section: Controlsupporting
confidence: 77%
“…Few studies with different methods, each of them in a small number of patients, have analyzed the immune reconstitution process after aHSCT for various types of autoimmune disease, including multiple sclerosis, 35 SSc, 29,30 juvenile arthritis 36 and SLE. 37 All studies reported that long-term remission in patients who received aHSCT was associated with a de novo regeneration of the T-cell compartment that can be delayed for years after T-cell depleting conditioning for aHSCT.…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent increase of Th1/Th2 ratios, 58 recovery of Treg function, 14 changes in thymic output, 19,33,59 and lower profibrotic serum cytokine levels 60 have been described. Several questions still remain, especially concerning the immunological determinants of clinical outcomes.…”
Section: Org Frommentioning
confidence: 99%
“…59 Additionally, a new study demonstrated immunological reconstitution obtained from suppression of thymic function after autologous HSCT in 10 patients with SSc, assessed by quantification of signal joint T cell receptor rearrangement excision circles (sjTREC). 60 The protocols of the ASTIS and SCOT trials are similar in their selection criteria, primary outcome and control arms, but differs in the conditioning regimens. ASTIS utilizes cyclophosphamide 200 mg/kg body weight and rabbit ATG, and SCOT uses cyclophosphamide 129 mg/kg body weight, equine ATG, and radiation of 800 cGy (with shielding of the lungs and kidney).…”
Section: Dovepressmentioning
confidence: 99%